Exploring the Intellectual Property Rights Potential of an Intangible Heritage - Hasbir Paserangi; Ahsan Yunus; Riyad Febrian Anwar (Jurnal Akta, 2022)
This Article discusses the unique and distinct characteristics of Songkok to Bone product as economic potential product with promising market share to reach countries such as Malaysia and Singapore. However, until now, this potential has not been accommodated with protective efforts to secure the intellectual property rights aspect of this product, namely geographical indications. The purpose of this study was to analyze the potential protection of intellectual property rights in the form of Geographical Indications for Songkok to Bone products. The approach method used in this research is a normative and empirical approach by reviewing the laws and regulations relating to Geographical Indications and conducting direct interviews with the local government of Bone Regency and Songkok To Bone craftsmen in Paccing Village and Compong e Village in the District of Awangpone, Bone Regency. The results showed that the ignorance of the craftsman community (including the local government in Bone Regency) about the importance of protecting intellectual property rights for the songkok to bone product as well as the economic benefits of the registration, became the driving factors that the Songkok To Bone product had not been registered as a Geographical Indication Rights for the people of the Bone Regency, especially by the Songkok To Bone craftsmen.